Answer:
x = - 2
Explanation:
Distribute
4(x + 1) = -3x - 10
4x + 4 = -3x - 10
Subtract 4 from both sides of the equation
4x + 4 = -3x - 10
4x + 4 − 4 = −3x − 10 − 4
Simplify
Subtract the numbers
4x+4−4=−3x−10−4
4 = − 3 − 1 0 − 4
Subtract the numbers again
4 = − 3 − 14
Add 3x to both sides of the equation
4 = − 3 x − 1 4
4 + 3 = − 3 − 1 4 + 3
Simplify
Combine like terms
4 + 3 = -3x-14+3x
7x =−3x−14+3x
Divide both sides of the equation by the same term
7 = − 1 4
7 /7 = -14/7
Cancel terms that are in both the numerator and denominator
7x/7 = -14/7
x = -14/7
Divide the numbers
= − 1 4 /7
= − 2